Zone 2 flexor tendon injuries: Our experience with early active movement protocol for rehabilitation of tendons (Annals of Medical Research, 2021)
None
Keywords: No man`s land; zone 2 flexor tendon; Kleinert`s protocol; Duran`s protocol.